Evaluation of Zebrafish (Danio rerio) as a biomedical model for determining the toxicity os lisdexanfetamine dimesylate (Research, Society and Development, 2022)
Zebrafish (ZF), scientific name Danio rerio, is increasingly used to perform tests involving the formation of neuronal circuits, behavior patterns and neuropatogeny, which allow toxicological studies involving the Central Nervous System. Thus, drugs that act in monoamine-related systems, such as dopamine and serotonin - fundamental in the regulation of brain functions in animals and humans - can be better studied from methods using ZF, which has specific components to capture these substances, allowing their evaluation.In this scenario, Lisdexamphetamine Dimesilate (DEX), a drug used to treat Attention Deficit Hyperactivity Disorder (ADHD), has properties capable of acting on the regulatory mechanisms of monoamines in order to minimize deficits caused by the disorder. Entretanto, devido a esses atributos, o DEX vem sendo utilizado por jovens e adultos hígidos, podendo trazer prejuízos devido a possíveis danos neurotóxicos. Com isso, este estudo objetiva por meio de uma revisão integrativa confirmar a aplicabilidade do modelo biomédico do ZF em avaliação de neurotoxicidade do DEX.